Albumin‐to‐fibrinogen ratio as a promising biomarker to predict clinical outcome of non‐small cell lung cancer individuals. (13th March 2018) - Li, Shu‐Qi; Jiang, Yu‐Huan; Lin, Jin; Zhang, Jing; Sun, Fan; Gao, Qiu‐Fang; Zhang, Lei; Chen, Qing‐Gen; Wang, Xiao‐Zhong; Ying, Hou‐Qun
Abstract: Chronic inflammation is one of the critical causes to promote the initiation and metastasis of solid malignancies including lung cancer (LC). Here, we aimed to investigate the prognostic roles of albumin (Alb)‐to‐fibrinogen (Fib) ratio (AFR), Fib and Alb in LC and to establish a novel effective nomogram combined with AFR. Four hundred twelve LC patients diagnosed between February 2005 and December 2014 were recruited in this prospective study. The prognostic roles of AFR, Fib, Alb, neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR) and monocyte‐to‐lymphocyte ratio (MLR) were identified by X‐tile software, Kaplan–Meier curve, Cox regression model, and time‐dependent ROC. Pretreatment high circulating Fib, low AFR, and Alb were significantly associated with increased risk of death for LC patients, especially for non‐small cell lung cancer (NSCLC) patients in all stages. The area under curves (AUCs) of AFR, Fib, and NLR were higher than them within Alb and PLR for predicting the survival of NSCLC patients. Moreover, we found that clinical outcome of high AFR patient with chemo‐radiotherapy was superior to low AFR patient; overall survival rate of stage II‐III NSCLC patients undergoing chemo‐radiotherapy was significantly lower than the surgical patients with treatment of adjuvant chemo‐radiotherapy( P  = 0.001) in low AFR subgroup. On the contrary, clinical outcome of the patients receiving chemo‐radiotherapy was the same to the patients undergoing surgery and adjuvant chemo‐radiotherapy ( P  = 0.405) in high AFR subgroup. In addition, c‐index of predicted nomogram including AFR (0.717) for NSCLC patients with treatment of chemo‐radiotherapy was higher than that without AFR (0.707). Our findings demonstrated that circulating pretreatment AFR might be a potential biomarker to predict clinical efficacy of surgical resection and adjuvant chemo‐radiotherapy and be a prognostic biomarker for NSCLC individuals. Abstract : Circulating pretreatment albumin to fibrinogen ratio was a promising prognostic biomarker of NSCLC. According to AFR, stage II–III NSCLC patients were received suitable therapeutic method and the predicted efficacy of nomogram was improved for NSCLC receiving chemo‐radiotherapy.